The graves are not yet full race, tribe and power in the heart of Africa - Berkeley, Bill. (New York : Basic Books, 2001)
The author presents situations and personalities of Africa as he knows them, along with the theory that "Africa's ruinous conflicts are not a product of age-old hatreds but of calculated tyranny."--Jacket.
A farmer -- The rebel -- The assistant secretary -- "A voice of good sense and good will" -- The collaborator -- Three Ph. D.s and a new kind of African leader -- The defendant.
Includes bibliographical references (p. 287-293) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on print version record.
Keywords: Insurgency -- Africa, Sub-Saharan.; Heads of state -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Politics and government -- 1960-; Africa -- Politics and government -- 20th century